Numerical simulation of detonation wave propagation and quenching process in in-line crimped-ribbon flame arrester. Issue 1 (1st January 2018) - Sun, ShaoChen; Shu, Yuan; Feng, Yu; Sun, DaChao; Long, HaiTao; Bi, MingShu
Abstract: A new numerical model for simulating the propagation and quenching of a detonation wave in in-line flame arrester was developed by using FORTRAN language. Accordingly, this study analysed the initiating process, quenching rule of a detonation wave in an arrester element and effect of arrester structural parameters on the propagation process of a detonation wave. Results showed that the quenching length of detonation wave increases with porosity, and the two parameters present a quadratic function relationship. Quenching length minimally varied with the increase in arrester thickness. The detonation wave collided with the element wall whilst porosity decreased when detonation wave propagated in the arrester element. Consequently, a pressure peak drop of the detonation wave was observed. As arrester thickness increased, the pressure peak of the detonation wave in the arrester element and the value of temperature on the position where the transmitted shock wave lies decreased, thereby cause a strong inhibition to the detonation wave. Simulation result showed that detonation pressure decreased progressively as porosity increased, and the two parameters exhibited a quadratic function relationship. By contrast, detonation pressure increased progressively as arrester thickness grew, and the two parameters presented a quadratic function relationship.